Effects of Training Programs on Decision-Making in Youth Team Sports Players: A Systematic Review and Meta-Analysis - Silva, Ana Filipa; Ramirez-Campillo, Rodrigo; Sarmento, Hugo; Afonso, José; Clemente, Filipe Manuel (Frontiers in Psychology, 2021)
Background: The use of dedicated training programs for improving decision-making (DM) in team sports players has grown in the last several years. Approaches such as imagery training, video-based training, or game-based drills are some of the interventions used in youth players in order to improve DM. However, no systematic reviews or meta-analyses have been conducted to summarize the main evidence regarding the effects of these programs on the players and identify the magnitude of the effects compared to control groups. Objective: This systematic review (with meta-analysis) was conducted to assess the effects of training programs on the DM of youth team sports players. Data sources: The data sources utilized were PubMed, PsycINFO, Scopus, SPORTDiscus, and Web of Science. Study eligibility criteria: The criteria included the following: (i) youth (≤18 years old) team sports players with no restriction on sex or competitive level; (ii) players subjected to training programs to develop DM; (iii) control groups; (iv) pre-post outcomes related to tactical behavior, technical execution, reaction, and decision time; and (v) controlled trials. Results: The database search initially identified 2,497 titles. From these, six articles were eligible for the systematic review and meta-analysis. The results showed a significant beneficial effect of DM interventions on tactical behavior (ES = 1.12; p = 0.035; I2 = 80.0%; Egger’s test p = 0.066), whereas no significant effect of DM interventions on technical execution was found (ES = 0.74; p = 0.180; I2 = 69.1%; Egger’s test p = 0.873). Conclusions: The DM interventions were significantly effective in improving tactical behavior in youth team sports players independently from the number of sessions to which players were exposed. In addition, DM interventions were significantly effective in improving technical execution. However, the results should be carefully interpreted due to the heterogeneity of the articles' overall methodological quality. Future DM interventions should consider using combined approaches that allow players to develop both tactical behavior and technical execution.